Different exposure levels of fine particulate matter and preterm birth: a meta-analysis based on cohort studies - Liu, Chenchen; Sun, Jiantao; Liu, Yuewei; Liang, Hui; Wang, Minsheng; Wang, Chunhong; Shi, Tingming (Environmental science and pollution research international, 2017)
The previous studies estimated the association between PM 2.5 (particulate matter with aerodynamic diameter less than or equal to 2.5 μm) exposure during pregnancy and preterm birth, only considered and highlighted the hazard effects of high levels of air pollutant exposure, and underestimated that low levels of pollutant exposure might also affect pregnancy outcome. We conducted a meta-analysis of 11 cohort studies, a total of more than 1,500,000 subjects. The results of these studies were pooled by exposure levels and study periods. PM 2.5 exposure during pregnancy was positively associated with preterm birth (OR = 1.15, 95% CI = 1.07–1.23), and during the first trimester of pregnancy, low levels of PM 2.5 exposure were also positively associated with preterm birth (OR = 1.17, 95% CI = 1.04–1.30). It is important to protect pregnant women from PM 2.5 exposures, especially during their first trimester of pregnancy even when the ambient PM 2.5 concentration is relatively low. More relevant health policy should be carried out to prevent hazard effect of air pollutants.